PENILAIAN KUALITAS AIR SITU PENGARENGAN, DEPOK, JAWA BARAT - Nabila, Cynthia; Hendrawan, Diana Irvindiaty; Astono, Widyo (Jurnal Lingkungan dan Kota, 2022)
Pangarengan shallow lake in Depok City has been polluted by the garbage that has accumulated in the area and its surroundings as well as the waste water that enters. Pangarengan shallow lake pollution is caused by community activities in the catchment area. The purpose of the study was to determine the water quality of Pangarengan shallow lake. Sources of pullutants that enter the Pangarengan come from surrounding settlements, cattle breeding, and other domestic activities such as stalls and tofu factories. Parameters measured were temperature, TSS, turbidity, pH, DO, BOD, nitrate, phosphate, COD, and E.coli. The air quality analysis will then be compared with the quality standard according to Government Regulation No. 22 of 2021. The status of water quality is determined by the pollution index method. BOD ranged from 4.78-11.90 mg/L, COD ranged from 38.40-86.40 mg/L, phosphate ranged from 0.05-0.29 mg/L, and E. coli ranged from 5,4x103-3,45x104 MPN/100 ml. The Pollutant Index of Pangarengan shallow lake is 5.34. The results of the Situ Pengarengan air quality analysis show that parameters still exceed the quality standards, that are BOD, COD,vphosphate, and E. coli and the water quality status of Pangarengan shallow lake is moderately polluted.